2019
DOI: 10.1109/tps.2018.2867431
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53-Mediated Apoptosis Pathway in HSC3 Cancer Cell Irradiated by Atmospheric DBD Oxygen Plasma

Abstract: Oral cancer cell HSC3 is inactivated by the direct irradiation of oxygen plasma generated by torch-type oxygen dielectric barrier discharge. Selective inactivation of the cancer cells is observed at the discharge voltage of 4.2 kV, where normal cells suffer no damages from the plasma. Inactivation mechanism of HSC3 cells irradiated by the plasma is considered as the apoptosis. Activation of mitogen-activated protein kinase and p53 proteins owing to the phosphorylation is one of the pathways to the cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Reactive species generated in the gas plasma phase can induce endoplasmic reticulum (ER) stress resulting in increased calcium influx into the mitochondria and mitochondria-dependent apoptosis 53 , 54 . Upon plasma-mediated activation of pro-apoptotic signaling cascades, an increase of Bax over Bcl2 55 , the release of mitochondrial cytochrome c 56 , and subsequent activation of p53 have been observed 57 . Alterations in signaling pathways in response to oxidative stress 58 60 may impair plasma treatment efficacy to display cytotoxicity in different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive species generated in the gas plasma phase can induce endoplasmic reticulum (ER) stress resulting in increased calcium influx into the mitochondria and mitochondria-dependent apoptosis 53 , 54 . Upon plasma-mediated activation of pro-apoptotic signaling cascades, an increase of Bax over Bcl2 55 , the release of mitochondrial cytochrome c 56 , and subsequent activation of p53 have been observed 57 . Alterations in signaling pathways in response to oxidative stress 58 60 may impair plasma treatment efficacy to display cytotoxicity in different cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these experimental in vitro studies used the oral squamous cell carcinoma cell line SCC-15, as well as SCC-25, and highlighted their plasma-induced inactivation due to the reduction of cell growth, induction of apoptosis, and secondary DNA damage, especially through plasma-derived ROS [19,25,28,[34][35][36][37][38]. Other HNSCC cell lines were also tested, showing one or more of the tumor-toxic plasma-associated characteristics [6,19,22,24,[26][27][28][29][30][31][32][33]37]. In addition, HNSCC has been shown to be more prone to physical plasma treatment than non-malignant cells since the viability of the latter did not significantly decrease after plasma application.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…Besides EGFR, studies suggested a crucial role of the p53-signaling pathway in plasma-induced head and neck cancer cell death [23,29,33,37]. This protein contributes to the redox balance within the cells via regulation of the antioxidant gene expression and further senses DNA damage, initiates signaling pathways for the DNA repair, and fulfills the role of a cell-cycle regulator [20].…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations